Analysis of the effect of process parameters on part wall thickness variation in conventional metal spinning of Cr-Mn austenitic stainless steels - Šugár, Peter (Strojniški vestnik, 2016)
Metal spinning is one of a number of flexible sheet forming processes which is a cost effective option for the production of parts with a very high strength to weight ratio. Although the wall thickness of the formed part in conventional spinning is generally considered to be nearly constant, a non uniform distribution of wall thickness is in fact observed. In this study, the wall thickness variation of a formed part made of Cr-Mn austenitic stainless steel was analysed. The thickness variation was measured using an optical 3D scanning method and the influence of mandrel speed, feed ratio and tool path profile (convex, concave and linear) on wall thickness variation was studied. A three-level full factorial design of the experiment and ANOVA (Analysis of Variance) were used. The results show that the maximal variation in wall thickness is observed in approximately half of the part wall height (thinning) and on the open end of the part (thickening). Feed ratio and roller path profile are statistically significant factors governing wall thickness variation. There was no obvious effect from the variation in mandrel speed on the thickness distribution.
Keywords: 3D-optično skeniranje; debelina stene; nerjavna jekla; rotacijsko preoblikovanje kovine